2023
DOI: 10.1007/s12298-023-01376-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar-dependent and drought-induced modulation of secondary metabolites, adaptative defense in Fagopyrum esculentum L

Sytar Oksana,
Kovar Marek,
Brestic Marian
et al.

Abstract: The present study investigates the biochemical responses of buckwheat to drought stress, particularly focusing on phenolic acids and flavonoids, abundant in this crop. We hypothesize that distinct genotypic responses to drought stress will lead to variations in phenolic acid accumulation. Two common buckwheat cultivars, Panda (East European origin) and PI 482597 (originating from Zimbabwe), were subjected to drought treatment, with biochemical traits, relative water content, and photosynthetic pigments regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The distinct clustering observed among all traits, particularly the identification of the XiNong 9943 genotype as exhibiting the highest drought tolerance. This result is consistent with prior research indicating the importance of RWC regulation, osmotic adjustment, and antioxidant defense mechanisms in conferring stress resilience [17,[65][66][67]. Overall, the integration of these analytical approaches enhances our understanding of genotypic responses to PEG-induced drought stress, elucidating key physiological and biochemical mechanisms underlying drought tolerance in Tartary buckwheat genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…The distinct clustering observed among all traits, particularly the identification of the XiNong 9943 genotype as exhibiting the highest drought tolerance. This result is consistent with prior research indicating the importance of RWC regulation, osmotic adjustment, and antioxidant defense mechanisms in conferring stress resilience [17,[65][66][67]. Overall, the integration of these analytical approaches enhances our understanding of genotypic responses to PEG-induced drought stress, elucidating key physiological and biochemical mechanisms underlying drought tolerance in Tartary buckwheat genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Sperdouli et al [21] moderate drought stress increased anthocyanin in Arabidopsis thaliana leaves by 2.9 times. Oksana et al [80] observed that in buckwheat (Fagopyrum esculentum L) the effect of drought stress on quercetin varied with different varieties. In this study, drought stress significantly increased the contents of six anthocyanins in drought-resistant variety Hequ red millet, increased the contents of isorhamnetin and kaempferol in drought-sensitive variety Yanshu No.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly negative correlation between 4-coumaric acid and the two proteins suggests reduction of the metabolite in the needles of I_D seedlings. However, some other experiments showed that 4-coumaric acid accumulated in plants under drought stress (Arabsalehi et al, 2023;Oksana et al, 2023). Its reduced level may be related to difference in plant species because Arabsalehi et al (2023) found decrease in level of quercetin, which often accumulated high levels in plants and played important physiological roles under drought stress (Gray et al, 2003;Singh et al, 2021).…”
Section: Serendipita Indica-induced Drought Tolerance By Improving Bi...mentioning
confidence: 99%